Intelligent data analysis and applications : proceedings of the Second Euro-China Conference on Intelligent Data Analysis and Applications, ECC 2015 /: proceedings of the Second Euro-China Conference on Intelligent Data Analysis and Applications, ECC 2015. ([2015]) - Unknown
No abstract available